2011
DOI: 10.4067/s0716-97602011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Testis-mediated gene transfer in mice: comparison of transfection reagents regarding transgene transmission and testicular damage

Abstract: Testis-mediated gene transfer (TMGT) has been used as in vivo gene transfer technology to introduce foreign DNA directly into testes, allowing mass gene transfer to offspring via mating. In this study, we used plasmid DNA (pEGFP-N1) mixed with dimethylsulfoxide (DMSO), N,N-dimethylacetamide (DMA) or liposome (Lipofectin) in an attempt to improve TMGT. Males receiving consecutive DNA complex injections were mated to normal females to obtain F0 progeny. In vivo evaluation of EGFP expression, RT-PCR and PCR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…However, Sato and Nakamura indicated that repeated injections (3 and 6 repeated injections, 3 days apart) were not critical for introducing high copy numbers of DNA into offspring (Sato & Nakamura, 2004). Furthermore, although DNA-DMSO complex could produce as many as 61%, 55%, and 80% of transgenic founders in mouse and/or rabbit through testes injection, DMSO-containing solution induces testicular degeneration and reduces vascularization around seminiferous tubules (Shen et al, 2006;Amaral et al, 2011). Notably, the efficiency of producing transgenic founder mice through one injection procedure performed in this study by applying BMPs was 88%, which was higher than existed reports.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, Sato and Nakamura indicated that repeated injections (3 and 6 repeated injections, 3 days apart) were not critical for introducing high copy numbers of DNA into offspring (Sato & Nakamura, 2004). Furthermore, although DNA-DMSO complex could produce as many as 61%, 55%, and 80% of transgenic founders in mouse and/or rabbit through testes injection, DMSO-containing solution induces testicular degeneration and reduces vascularization around seminiferous tubules (Shen et al, 2006;Amaral et al, 2011). Notably, the efficiency of producing transgenic founder mice through one injection procedure performed in this study by applying BMPs was 88%, which was higher than existed reports.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the most popular methods in producing such animals remains low efficiency, which either requires high technologies, expensive instruments, has safety risks or brings adverse effects upon cells and tissues (Smith, 2004;Parrington et al, 2011), and as a result, are not easily handled by individual laboratories. Previously developed spermatozoa-based gene transfer methods, including testis-and sperm-mediated gene transfer (TMGT and SMGT) can be performed by general researchers to achieve personalized gene modifications in animals (Coward et al, 2007;Collares et al, 2010;Amaral et al, 2011;Campos et al, 2011a,b). Referring to TMGT, foreign DNA vehicles need to be excellent in penetrating thick tissues to achieve better output.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that DMSO acts as a free-radical scavenger against the effects of radiation and helps preserve some male fertility [ 24 ]. Possible causes of impaired male fertility could be the number of injections in testicles and cell damage, since DMSO with DNA used as a transfection agent causes marked histological changes in seminiferous tubules [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both transcription factors have a synergistic effect, revealing a central role for Sox in the Catsper1 gene transcription [ 16 ]. The Catsper1 promoter has not been evaluated in the testicular environment [ 17 , 18 , 19 , 20 , 21 , 22 ], where Sox factors could affect its activity as they do in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, He et al [53] demonstrated that the transgene transmission rate from F0 to F1 generation was 37%, suggesting that the transgene transmission rate was similar to the Mendelian law of inheritance. In 2007 and onward, attempts to improve IIGT systems were made by several laboratories to enhance the gene delivery efficiency [54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In the following sections, we will describe several examples [(v) to (x)] about the improvement of IIGT, in vitro assessment for gene expression after IIGT or possible mechanism underlying IIGT.…”
Section: Historical Background Of Tmgt-related Experiments 21 Iigt-rmentioning
confidence: 99%